Flowering capacity and botanical seed production of sweet potato genotypes - Brito,Orlando G (2021)
ABSTRACT The identification of genotypes with greater capacity for flowering and seed production is crucial for greater efficiency in the genetic improvement of the sweet potato crop. Thus, the objective of this work was to evaluate the flowering capacity and the production of botanical seeds in sweet potato genotypes. The work was carried out in the municipality of Lavras, located in the southern region of Minas Gerais, Brazil. Twenty-two sweet potato genotypes belonging to the germplasm bank of the Federal University of Lavras (UFLA) were evaluated. The characteristics evaluated were the flowering period (days), the number of viable seeds, the total weight of viable seeds, the weight of 1000 seeds and the percentage of germination. The obtained data were analyzed by means of descriptive statistics, study of correlations and analysis of main components. The sweet potato genotypes evaluated showed a high capacity for flowering and production of botanical seeds. Flowering usually starts 125 days after planting and extends on average for 72 days. Considering future recombination to promote flowering capacity, seed production and greater germination, genotypes BD-05, BD-26 and BD-44 should be prioritized.